Sovereign Wealth Funds in East Asia - Seward, James; Ulukan, Mustafa; Kim, Mee Jung; Tsubota, Hiroshi; Gable, Timothy (World Bank, Washington, DC, 2015)
Sovereign Wealth Funds (SWFs) have been in existence for many decades worldwide, however most SWFs in the East Asia and Pacific Region (EAP) are relatively new. The emergence of the SWFs in Asia is largely a by-product of the strong economic development at East Asian countries in the last two decades and the attendant accumulation of foreign exchange reserves. However, there are other types of SWFs in the region as well. The EAP region is an ideal region to take a look at the issues surrounding SWFs since Asia has the full range of funds from long-established funds to brand new funds; from passive portfolio investors to more aggressive strategic investors; from resource-backed funds to foreign reserve-backed funds; and, based in the largest, most highly developed economies to the smallest, poorest economies in Asia. Therefore, the objective of this report is to document the status of Sovereign Wealth Funds in the East Asia Region and to understand their governance structures. The report will also investigate how lack of standardized, long-term financial instruments devoted to emerging markets leads funds to leak out of the EAP region, an area with significant investment needs. It presents facts from publicly available sources on their size, institutional structure, and investment operations.